The selecting of roofing material for pitched roofs by the analytic hierarchy process - Romanova Irina; Skanavi Nataliya (MATEC Web of Conferences, 2017)
Today’s in the market of building materials there are a large number of roofing materials for pitched roofs. All of these materials have their advantages and disadvantages, so the task of choosing the optimal option is complex and requires special methods to eliminate the subjectivity of evaluation. The article describes the approach to selecting the best option of roofing material from the available options by the set of its quantitative and qualitative characteristics. It is proposed to carry out the evaluation of options and selection of the best option based on the analytic hierarchy process. The article presents the results of the selection of the most appropriate roofing material for pitched roofs using the specified method.